2014
DOI: 10.1186/1556-276x-9-459
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress mediated cytotoxicity of biologically synthesized silver nanoparticles in human lung epithelial adenocarcinoma cell line

Abstract: The goal of the present study was to investigate the toxicity of biologically prepared small size of silver nanoparticles in human lung epithelial adenocarcinoma cells A549. Herein, we describe a facile method for the synthesis of silver nanoparticles by treating the supernatant from a culture of Escherichia coli with silver nitrate. The formation of silver nanoparticles was characterized using various analytical techniques. The results from UV-visible (UV-vis) spectroscopy and X-ray diffraction analysis show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 77 publications
6
108
0
1
Order By: Relevance
“…13,[85][86][87][88] Recent studies suggest a potential link between ROS regulation and autophagic processes, because agents capable of inducing ROS formation play a crucial role in the induction of autophagy in embryonic kidney HEK293 cells, human fibroblast HT1080 cells, and human lung cancer cells. 84,89,90 For instance, platinum-based therapy and epigallocatechin gallate-mediated cell death may also depend on the generation of ROS either directly or indirectly. 91,92 A recent study suggested that Cis induces autophagy in HeLa cells via upregulating the formation of autophagic vesicles, promoting the conversion of LCI to LCII and increasing the expression of the autophagy-related ATG7 gene.…”
Section: Combination Of Cis and Rgo-agnps Induces Accumulation Of Autmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[85][86][87][88] Recent studies suggest a potential link between ROS regulation and autophagic processes, because agents capable of inducing ROS formation play a crucial role in the induction of autophagy in embryonic kidney HEK293 cells, human fibroblast HT1080 cells, and human lung cancer cells. 84,89,90 For instance, platinum-based therapy and epigallocatechin gallate-mediated cell death may also depend on the generation of ROS either directly or indirectly. 91,92 A recent study suggested that Cis induces autophagy in HeLa cells via upregulating the formation of autophagic vesicles, promoting the conversion of LCI to LCII and increasing the expression of the autophagy-related ATG7 gene.…”
Section: Combination Of Cis and Rgo-agnps Induces Accumulation Of Autmentioning
confidence: 99%
“…Recently, Han et al observed that the AgNPs induced accumulation of autophagosomes and autolysosomes in human lung carcinoma cells and combination of salinomycin and AgNPs enhanced the expression of various autophagy genes and accumulation of autophagosomes, lysosomes, and autophagolysosomes in human ovarian cancer cells. 13,84 Once autophagosomes are formed, they can merge with lysosomes to form autolysosomes, whose contents are degraded by lysosomal hydrolases. 81 Although autophagy seems to protect cells against cell death under oxidative stress, extended autophagy can induce cell death in several cases, such as precancerous cells.…”
Section: Combination Of Cis and Rgo-agnps Induces Accumulation Of Autmentioning
confidence: 99%
“…111 Furthermore, another study on the combination of AgNPs and salinomycin also resulted in extensive ROS generation in human ovarian cancer cells, and eventually, the combination induced accumulation of APs and autolysosomes/autophagic vacuoles. 81 Consistent with our results, previous studies also reported that GO can enter the cells by interacting with the plasma membrane and probably temporarily disrupting the phospholipid bilayer or causing plasma membrane invagination in HepG2 cells and neuroblastoma cell lines, including SK-N-BE(2) and SH-SY5Y.…”
mentioning
confidence: 99%
“…The peaks at 1060 cm − 1 (C-O stretching vibrations), 1245 cm−1(C-OH stretching vibration) and 1725 cm − 1 (C=O stretching vibration) were become less intense; which suggests the reduction of graphene. The peaks in between 2924 cm − 1 to 3400 cm − 1 of silver were assigned to the stretching vibrations of primary and secondary amines, while their corresponding bending vibrations were seen at 1383 cm − 1 and 1636 cm − 1 respectively [56]. The wave number positioned around 1700 cm −1 was attributed to the stretching vibration of the C=O group (ester carbonyl) in the PHA.…”
Section: Ftir Analysismentioning
confidence: 99%